Increased Nitrogen Availability in the Soil Under Mature Picea abies Trees Exposed to Elevated CO2 Concentrations - Schleppi, Patrick; Körner, Christian; Klein, Tamir (Frontiers in Forests and Global Change, 2019)
The response of trees to increasing atmospheric CO2 concentrations is often mediated by the availability of nutrients. However, little is known about the influence of CO2 enrichment on nutrient availability in forests with mature trees. We studied processes in the soil under five 35-m-tall Norway spruce trees (Picea abies) in NW Switzerland that were exposed to a mean CO2 concentration of 550 ppm for 5 growing seasons using free air CO2 enrichment (FACE). We compared them with values from the soil under five control trees. Ceramic suction cups were installed in the soil under each tree to collect soil solution, and ion-exchange resin bags were buried in the soil to absorb ammonium and nitrate. Soil cores taken at the end of the experiment were used to measure the gross production of ammonium and nitrate by the 15N dilution technique. Although temporally and spatially variable, the nitrate concentration was higher in the soil solution under CO2-enriched trees. This effect was reflected in the resin bag extracts, which additionally indicated a trend of increased ammonium availability. Dissolved reduced N concentration (mainly dissolved organic N), however, was lower in the soil solution under CO2-enriched trees. K and Mg, and to a lesser extent Na and sulfate concentrations increased in the soil solution. P concentrations mostly remained below the detection limit. In spite of the higher concentrations of nitrate in soil extracts, gross N mineralization and nitrification rates were not affected by FACE. Needles from CO2-enriched trees contained slightly more N. No difference was observed for other nutrients. Overall, these results support the hypothesis of a priming effect, i. e. that FACE led to the production of more root exudates, which in turn stimulated soil biological activity, including mineralisation, over a time-span of at least several years. However, these tall trees showed no growth response to elevated CO2; hence, they gained no advantage from increased nitrate in the soil solution, presumably owing to other growth constraints including P and Mg availability.